Effect of heat treatment on microstructure and performances of additively manufactured 15-5PH stainless steel. (January 2023) - Chen, Wei; Xu, Lianyong; Hao, Kangda; Zhang, Yankun; Zhao, Lei; Han, Yongdian; Liu, Zhenyu; Cai, Haoyu
Highlights: The effects of microstructure evolution on mechanical properties and corrosion resistance of additively manufactured 15-5PH steel were analyzed. The complete crystal structure transformation of Cu-rich precipitates was revealed. The tuning mechanism of aging temperatures on the precipitation behavior and mechanical properties was investigated. Abstract: Effective post-processing heat-treatment is essential to obtain desired material properties of additively manufactured components. In this paper, the 15-5PH stainless steel (SS) samples were manufactured by laser directed energy deposition technology, and different heat treatments were employed for performance improvements. The microstructural evolution and its effects on mechanical performances and corrosion resistance of the 15-5PH SS specimens were thoroughly characterized and analyzed. The results show that the copper-rich precipitates (CRPs) play a critical role in the strengthening, and the structural transformation and coarsening of CRPs after the aging temperature exceeds 560 °C can lead to the rapid loss in strength and hardness, and the deterioration of corrosion performance. Moreover, when the aging temperature exceeds 560 °C, the toughness and ductility of 15-5PH SS increase with the aging temperature due to the massive formation of the soft reversed austenite.